Fitoplancton costero de Puerto Chicama, (Provincia de Ascope), La Libertad - Colchado Colchado, Jean Paul Edú (2017)
In the present investigation carried out in the coastal zone of Puerto Chicama in the period of February 2016 - year 2017, the evaluation of the phytoplankton was done resulting in a total of 82 species. Diatoms were the most numerous, with 51 species being the genus Chaetoceros most abundant, followed by dinoflagellates with 29 species being Protoperidinium the most abundant genus; We also found the silicoflagellates Ebria tripartita and Dictyocha fibula and their varieties. The physical-chemical parameters varied in the months of sampling; Being the temperature the parameter that fluctuated more obtaining 15.3 ° C as minimum value and 25.1 ° C as maximum value followed by salinity with values of 34.7 - 35.3 ppt.